PENGARUH PARASOCIAL INTERACTION TERHADAP PURCHASE INTENTION PENGGUNA SOMETHINC - HANIFA, NYAYU TASYAPUTRI; GULO, YUPITER (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this study was to determine the effect of parasocial interaction, transparency, perceived enjoyment, credibility and informativeness on the purchase intention of Somethinc users in DKI Jakarta. The sampling technique applied purposive sampling using a sample of 200. Research data was processed using the Structural Equation Model (SEM) analysis method. The research results show that parasocial interaction, credibility, and informativeness have a significant effect on purchase intention, either directly or mediated by credibility and informativeness. Meanwhile, transparency and perceived enjoyment do not have a significant effect on purchase intention, either directly or mediated by transparency and perceived enjoyment